Risk assessment of potentially toxic elements in street dust from Mahd Ad Dhahab gold mine, Saudi Arabia - Atef M. Abu Khatita (Journal of Taibah University for Science)
The current study evaluated the contamination level of potentially toxic elements (PTEs) and their associated risk in street dust in the vicinity of Mahd Ad Dhahab gold mine, KSA. 25 street dust samples were collected and then subjected to magnetic susceptibility (χ) measurements and analysed for Al, As, Cd, Co, Cr, Cu, Fe, Hg, Mg, Mn, Pb and Zn contents. The results revealed that the study area is contaminated by Cd, Zn, Hg, Cu, Pb and As, since their concentrations were higher than the background and displayed high values of coefficient of variation (41.86, 14.9, 11.05, 10.1, 8 and 5.3, respectively) combined with high enrichment factor (181.7, 167.5, 183.6, 122.8, 151.7 and 33.95, respectively). The higher concentrations of these elements, associated with higher χ values, were recorded close to the mining area. The correlation coefficient and heatmap categorized the studied PTEs into two groups; The first group comprised Al, Co, Cr, Fe, Mg and Mn of geogenic origin; the second included As, Cd, Cu, Hg, Pb and Zn, along with χ, which controlled by anthropogenic sources. Ecological risk assessment values indicated that 28% of the samples have very strong ecological risk. Regarding human health risk, among different pathways, ingestion is a primary pathway of PTEs harming human health. The non-carcinogenic risks from Cd, Cu and Pb and carcinogenic risk from As exceeded the acceptable level to local children. The study demonstrated that mining activities are the main source of street dust contamination in the area.